The focus group technique in library research: an introduction. - Glitz, B (1997)
The focus group technique is one example of a qualitative research methodology used to explore the opinions, knowledge, perceptions, and concerns of individuals in regard to a particular topic. The focus group typically involves six to ten individuals who have some knowledge of or experience with the topic. The group discussion is led by a moderator who guides participants through a series of open-ended questions. The information gathered can provide important clues to human attitudes and values as they relate to the topic. Such information can be extremely useful to libraries that are trying to gain a better understanding of their patrons' needs and thus make better management decisions to help satisfy those needs. The technique can also be used successfully in conjunction with other research tools, such as surveys, either to help develop a questionnaire or to explain specific survey results. This paper introduces the use of focus groups in library research, the skills needed to conduct groups, and their strengths and weaknesses. Examples of the use of focus groups in health sciences libraries are presented, including the results of a survey from these libraries.